2006
DOI: 10.1242/jeb.02093
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acclimation temperature and cadmium exposure on cellular energy budgets in the marine molluskCrassostrea virginica: linking cellular and mitochondrial responses

Abstract: SUMMARY In order to understand the role of metabolic regulation in environmental stress tolerance, a comprehensive analysis of demand-side effects (i.e. changes in energy demands for basal maintenance) and supply-side effects (i.e. metabolic capacity to provide ATP to cover the energy demand) of environmental stressors is required. We have studied the effects of temperature (12, 20 and 28°C) and exposure to a trace metal, cadmium (50 μg l–1), on the cellular energy budget of a model marine poiki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(88 citation statements)
references
References 46 publications
4
82
1
1
Order By: Relevance
“…Within the thermal tolerance range, a rise in temperature results in a proportional increase in different aspects of the standard metabolic rate, including costs of protein synthesis, ATP turnover, mitochondrial proton leak and nonmitochondrial respiration (Cherkasov et al 2006a). Beyond the tolerance range at the pejus and upper critical temperatures, some cellular maintenance costs (especially costs of mitochondrial maintenance due to the proton leak) may increase disproportionately at the expense of other cellular functions (Pörtner 2001).…”
Section: Energy Demandmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the thermal tolerance range, a rise in temperature results in a proportional increase in different aspects of the standard metabolic rate, including costs of protein synthesis, ATP turnover, mitochondrial proton leak and nonmitochondrial respiration (Cherkasov et al 2006a). Beyond the tolerance range at the pejus and upper critical temperatures, some cellular maintenance costs (especially costs of mitochondrial maintenance due to the proton leak) may increase disproportionately at the expense of other cellular functions (Pörtner 2001).…”
Section: Energy Demandmentioning
confidence: 99%
“…the amount of metabolic energy required for the basal maintenance and survival of the individual) (Sibly & Calow 1989, Calow & Forbes 1998; however, unlike temperature, metal exposures typically lead to a disproportionate increase in the aspects of cell metabolism responsible for cellular detoxification and repair (Sibly & Calow 1989, Calow & Forbes 1998, Cherkasov et al 2006a, Ivanina et al 2008a). Our studies showed that both protein synthesis rate and oxygen consumption required to cover the costs of protein synthesis increased in eastern oysters Crassostrea virginica exposed to Cd (Cherkasov et al 2006a, Ivanina et al 2008a). An increase in the cellular protein synthesis in metal-exposed oysters was associated with an elevated expression of cellular protection proteins, such as metallothioneins, P-glycoproteins and heat shock proteins (Ivanina & Sokolova 2008, Ivanina et al 2008a.…”
Section: Energy Demandmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated temperature led to an increase in mitochondrial respiration and the flux through the three studied mitochondrial subsystems in oysters, as is typical for ectotherm mitochondria (Abele et al, 2002;Blier and Guderley, 1993;Chamberlin, 2004b;Cherkasov et al, 2006a;Sokolova, 2004).…”
Section: Elevated Temperature and CD Modulate Mitochondrial Bioenergementioning
confidence: 60%
“…This suggests that in addition to the direct effects of Cd present in the cytosol and mitochondria, there are also slight but persistent shifts in the properties of oyster mitochondria induced by long-term Cd exposure that can contribute to the disturbance of energy metabolism in Cd-exposed oysters (Cherkasov et al, 2006a;Sokolova et al, 2004;Sokolova et al, 2005b). The molecular mechanisms of these shifts are currently unknown but may involve ROS-induced damage to mitochondrial enzymes due to the prooxidant effects of Cd (Cherkasov et al, 2007a;Valko et al, 2005;Wang et al, 2004).…”
Section: +mentioning
confidence: 99%